Exploration of the Role of Professional Ethics in Enhancing Internal Audit Quality in the Banking Sector - Hendro Lukman; Amatus Venantius Sabubun; Subur Harahap (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the crucial role of professional ethics—integrity, objectivity, independence, and competence—in enhancing internal audit quality in Indonesia’s banking sector. Using a mixed methods approach, quantitative data were collected from 80 internal auditors and analyzed through multiple regression, while qualitative insights were obtained from interviews with 15 audit managers and audit committee members. The findings show that professional ethics significantly improve audit quality, with integrity and independence being the strongest determinants of audit credibility, and competence reinforcing the reliability of audit recommendations. The qualitative results further highlight that an ethical organizational culture supports effective audit functions, strengthens governance, and helps prevent fraud. Overall, the study concludes that strong professional ethics not only elevate internal audit quality but also contribute to theoretical understanding and policy development for improving regulation and oversight in the banking industry.